Eksplorasi Beban Digital Guru: Survei Pemanfaatan Platform Merdeka Mengajar (PMM) oleh Guru - Haeri, Iman Zannatul; Afriansyah, Anggi (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2024)
Previous research has identified various challenges in the implementation of the Platform Merdeka Mengajar (PMM) among teachers, including limited internet access and technological devices, teachers' proficiency in using technology, limited understanding of PMM, and an increased digital workload that occupies teachers' time. This article aims to: (1) analyze the increase in teachers' digital workload due to extensive digitalization through PMM; (2) identify communication and instructional patterns in PMM implementation; and (3) examine how teachers utilize PMM to provide more effective and humane recommendations for improvement. A survey was conducted using a questionnaire distributed via Google Forms to 211 teachers across 27 provinces in Indonesia. The article highlights three key findings: First, digitalization through the Platform Merdeka Mengajar (PMM) significantly increases teachers' workload. A total of 55.9% of teachers reported teaching 24–30 hours per week, 19% taught 30–40 hours, and 4.3% taught 40–50 hours. Additionally, 79.1% of respondents indicated that PMM increased their administrative burden. Second, communication and instructions related to PMM were found to be hierarchical and lacked dialogue, with 70.1% of teachers using PMM due to direct instructions from the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) or school management. Third, the digital workload forced 51% of teachers to complete PMM tasks outside of school hours, including 22.3% working at home and 14.7% working late at night. Moreover, a significant portion of teachers relied on personal resources, with 71.1% using their own internet and 67.3% covering electricity costs to fulfill PMM requirements. This article recommends that the government consider teachers' rights and working hours when implementing PMM.AbstrakRiset terdahulu memaparkan berbagai tantangan dalam operasionalisasi Platform Merdeka Mengajar (PMM) di kalangan guru: keterbatasan akses internet dan perangkat teknologi, kapabilitas guru dalam penguasaan teknologi, pemahaman terbatas mengenai PMM, serta meningkatnya beban digital yang menyita waktu guru. Artikel ini bertujuan untuk: pertama, menganalisis peningkatan beban digital guru akibat masifnya digitalisasi melalui PMM; kedua, mengidentifikasi pola komunikasi dan instruksi dalam pengerjaan PMM; serta ketiga, meninjau ulang mekanisme pemanfaatan PMM oleh guru untuk memberikan rekomendasi perbaikan yang lebih efektif dan manusiawi. Survei dilakukan dengan menggunakan kuesioner yang disebarkan melalui Google Form kepada 211 guru di 27 provinsi di Indonesia. Tiga temuan utama artikel ini adalah: pertama, digitalisasi melalui PMM secara signifikan meningkatkan beban kerja guru. Sebanyak 55,9% guru mengajar 24-30 jam per minggu, 19% mengajar 30-40 jam, dan 4,3% mengajar 40–50 jam. Sebagian besar responden (79,1%) melaporkan bahwa PMM menambah beban administrasi mereka. Kedua, pola komunikasi dan instruksi terkait PMM bersifat hierarkis dan kurang dialogis, dengan 70,1% guru menggunakan PMM karena tekanan instruksi langsung dari Kemendikbudristek atau pihak sekolah. Ketiga, beban kerja digital memaksa 51% guru mengerjakan tugas PMM di luar jam sekolah dan mengerjakan di rumah (22,3%), sering hingga larut malam (14,7%), dan sebagian besar menggunakan biaya pribadi untuk internet (71,1%) dan listrik (67,3%). Artikel ini menyarankan DPR RI mendorong pemerintah untuk mempertimbangkan hak dan jam kerja guru dalam implementasi PMM.